Measuring and managing radiologist workload: A method for quantifying radiologist activities and calculating the full‐time equivalents required to operate a service. Issue 5 (12th July 2013) - MacDonald, Sharyn LS; Cowan, Ian A; Floyd, Richard A; Graham, Rob
Abstract Introduction Accurate and transparent measurement and monitoring of radiologist workload is highly desirable for management of daily workflow in a radiology department, and for informing decisions on department staffing needs. It offers the potential for benchmarking between departments and assessing future national workforce and training requirements. We describe a technique for quantifying, with minimum subjectivity, all the work carried out by radiologists in a tertiary department. Methods Six broad categories of clinical activities contributing to radiologist workload were identified: reporting, procedures, trainee supervision, clinical conferences and teaching, informal case discussions, and administration related to referral forms. Time required for reporting was measured using data from the radiology information system. Other activities were measured by observation and timing by observers, and based on these results and extensive consultation, the time requirements and frequency of each activity was agreed on. An activity list was created to record this information and to calculate the total clinical hours required to meet the demand for radiologist services. Results Diagnostic reporting accounted for approximately 35% of radiologist clinical time; procedures, 23%; trainee supervision, 15%; conferences and tutorials, 14%; informal case discussions, 10%; and referral‐related administration, 3%. The derived data have been proven reliable for workload planning over the past 3 years. Conclusions A transparent and robust method of measuring radiologists' workload has been developed, with subjective assessments kept to a minimum. The technique has value for daily workload and longer term planning. It could be adapted for widespread use.